Evaluation of GPR surveys for assessment of trees condition in urbanized areasbanized areas - Mazurek, Ewelina; Łyskowski, Mikołaj (Geology, Geophysics and Environment, 2015)
Modern measuring equipment is sometimes used for applications, for which it has not been originally designed. For example Ground Penetrating Radar (GPR), designed for subsurface structures analysis, can be used for tree tomography. Radar utilizes the phenomenon of propagation of the electromagnetic waves in a physical medium. Measurements can be carried out in situ, in a non-invasive manner on a living tree. Collected data allow for the tree condition determination. It is possible to detect voids and internal structure. Geophysical investigations can provide an estimation of the risk of falling of the trees. These methods also allow determination of the production quality of the tree by detecting knots inside the structure. Available literature shows only limited examples of the usage of other geophysical surveys, such as the ultrasound and geoelectrical method. However, in many cases these measurements are performed on samples in the form of profiles cut from the felled trees. Presented study was conducted on a set of 8 ash trees growing in the Krakow city parks. The measurement was carried out with high frequency antenna – 1600 MHz. Due to the lack of available literature and limited experience of the authors, only trees with known condition were tested. Despite many attempts, the authors were not able to developed a reliable measurement methodology which would allow for unambiguous classification and interpretation of results. In most cases, the results of the study permitted determination of the trees condition. However, some echograms, of the surveyed trees with visible voids pointed to a different tree state and misclassification. Despite that, the research results seem to be promising and the authors believe in the usefulness of the further development of measurement method along with its extension to other trees species.